Teachers’ perspectives on language policies for hard-of-hearing children : a case study on Canossian School - Chee, Clara Wenxin (Nanyang Technological University, 2020)
In recent years, there has been an increase in the recognition of linguistic rights for minority linguistic communities, including that of the right to sign language for the Deaf. At the same time, the proliferation of technology has made assistive devices for the deaf such as hearing aids and cochlear implants more accessible than ever. The medical and cultural views of the Deaf community have long been at conflict, which has had a constant impact on language policies for education. Oralism based approaches may seem straightforward, but such programmes reflect the two long-standing clashing views between the integration of a deaf child into mainstream society and right to a natural language. As the agents implementing the language policy, teachers of the deaf provide a glimpse of the complexity in language policy and planning for deaf education through the sharing of their attitudes and beliefs. This paper sets out to examine the teachers’ perspectives behind the language policies of an oral school for deaf children in Singapore, where research in deaf education is an extremely new and undocumented field. Semi-structured interviews were conducted with five teaching staff from a Special Education school for deaf children with an oral programme. An analysis of the interview brings to light the struggles and complexities of implementing an oral programme, as well as the covertly ambivalent attitudes the teaching staff have towards sign language.